2012
DOI: 10.2139/ssrn.2020177
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave Policies and Child Care Time in Couples after Childbirth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Contrary to studies in Sweden (Haas and Hwang 2008), the US (Nepomnyaschy and Waldfogel 2007) and the UK (Tanaka and Waldfogel 2007), they found ''limited support for the view that fathers leave taking at the time of the birth of a child is related to increased involvement of fathers in the care of the child' ' (2010: 1314). On the other hand, availability and length of maternity leave is strongly associated with mothers' time with children and their return-towork decisions (Pronzato 2009;Schober 2012;Whitehouse et al 2012). Particularly, unpaid maternity leave and flexible working hours are associated with greater likelihood that mothers will return to work after childbirth (Buddelmeyer and Fok 2007).…”
Section: Work and Childcare: Existing Researchmentioning
confidence: 99%
“…Contrary to studies in Sweden (Haas and Hwang 2008), the US (Nepomnyaschy and Waldfogel 2007) and the UK (Tanaka and Waldfogel 2007), they found ''limited support for the view that fathers leave taking at the time of the birth of a child is related to increased involvement of fathers in the care of the child' ' (2010: 1314). On the other hand, availability and length of maternity leave is strongly associated with mothers' time with children and their return-towork decisions (Pronzato 2009;Schober 2012;Whitehouse et al 2012). Particularly, unpaid maternity leave and flexible working hours are associated with greater likelihood that mothers will return to work after childbirth (Buddelmeyer and Fok 2007).…”
Section: Work and Childcare: Existing Researchmentioning
confidence: 99%
“…Schoenberg and Ludsteck (2007) found that after the reform 8 per cent of mothers delayed their labour market return and subsequently earned lower wages partly as a result. Longer maternal time-outs were also associated with a more traditional division of housework and child care in West German couples during the first years after childbirth (Schober, 2012; Schulz and Rost, 2012).…”
Section: Theoretical Framework For Parental Leave Policy Effects On Dmentioning
confidence: 99%
“…Moreover, childcare benefits to be paid to the mother during the leave are fixed and do not depend on previous earnings, while childrearing benefits are means-tested and dual earner families are typically ineligible. 7 This legislation has been proven to adversely affect women's labor supply, see Merz (2004) and Schober (2012), further reinforcing the existing prejudices delineated by Treas and Widmer (2000).…”
Section: The Case Of Germanymentioning
confidence: 99%